ADAPTATION PROCESSES IN CROSS - CULTURAL COMMUNICATION WITHIN CHINESE - INDONESIAN WORKPLACE SETTINGS: AN ANALYSIS OF THE TIKTOK SERIES "DAY 1 KERJA SAMA ORANG CHINA. " - Jie, Shi; Burhan, Amelia (International Review of Humanities Studies, 2026)
In the background ofChina's deepening economic engagement with Indonesia under the Belt and Road Initiative, increasing numbers of Chinese workers have entered Indonesian industrial zones, creating a workplace environment characterized by intensive cross-cultural interaction. While previous studies on cross-cultural adaptation have primarily emphasized macro-level cultural barriers and language difficulties, this research shifts attention to the micro-level communicative practices through which cultural adaptation is negotiated in everyday collaboration. Drawing on Howard Giles' Communication Accommodation Theory (CAT), this study conducts a qualitative analysis of TikTok videos depicting workplace interactions between Chinese and Indonesian workers particularly those labeled "Day 1 kerja sama orang China." Through analysis of high-engagement videos, the study identifies three communication strategies that Chinese and Indonesian workers employ under conditions of language barrier: technology-mediate translation, multimodal non-verbal communication, and creative expressions emerging from shared labor experience. These strategies operate not as sequential stages but as complementary forms of convergence through which both groups actively reduce communicative friction, sustain cooperation, and co-construct shared meaning. Findings indicate that cross-cultural adaptation among Sino-Indonesian laborers is not a product of unilateral assimilation but a cumulative result of repeated attempts to understand and be understood, leading to the emergence of pragmatic hybrid workplace expressions and a growing sense of shared identity. At the digital level, TikTok functions as a mediator that amplifies and reframes cross-cultural communication, normalizing everyday cooperation while simultaneously risking the reproduction of entertainment-driven stereotypes.